ANALISIS PENGARUH PAJAK REKLAME, PAJAK PENERANGAN JALAN DAN PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH DI KOTA PANGKALPINANG - Mega Aprilia Besa, Lestisia; Budi Marwoto, Pan; Oktalina, Gayatria (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This study uses Location Quotient Analysis (LQ) and multiple linear regression is also carried out hypothesis testing which will be proven by the t test and f test with a probability level of 5% of the research also presents R2 and multicollinearity tests. The results of LQ analysis are Advertisement Taxes, Road Lighting Taxes and Parking Taxes have comparative advantages compared to other taxes. Advertisement Tax has a LQ value of 1.01, Street Lighting Tax has a LQ value of 0.89 and Parking Tax has a LQ value of 1.08 which has a comparative advantage if the value of LQ = 1 And the value of LQ> 1, Advertising Tax, Tax on Street Lighting and Parking tax is chosen to be analyzed for its effect on local revenue because these taxes provide receipts every month and have a comparative advantage.